Gastrocnemius thickness by ultrasonography indicates the low skeletal muscle mass in Japanese elderly people. (September 2020) - Yuguchi, Satoshi; Asahi, Ryoma; Kamo, Tomohiko; Azami, Masato; Ogihara, Hirofumi
Highlights: Ultrasonography can evaluate the quality and quantity of a muscle. Gastrocnemius thickness by ultrasonography is independently associated with the low SMI. The cut-off value of gastrocnemius thickness to indicate the low SMI was <11.6 mm. Gastrocnemius thickness could be an alternative indicator for the low SMI easily and noninvasively. Abstract: Background: This study aimed to examine the relationship between gastrocnemius thickness by ultrasonography and the skeletal muscle mass in Japanese elderly people. Methods: The total of 195 healthy Japanese aged ≥65 years participated (average age, 72.4 ± 4.3y; male, n = 72). The skeletal muscle mass index (SMI) was measured using the bioelectrical impedance analysis (BIA) and the gastrocnemius thickness and collected echo intensity (CEI) were measured using ultrasonography. The low SMI was defined as <7.0 kg/m 2 in men and <5.7 kg/m 2 in women, and participants were classified into the low SMI and the normal group. Association of the gastrocnemius thickness with the low SMI was analyzed by the logistic regression analysis after adjusting age, gender, body mass index (BMI), physical performances and CEI. The cut-off value of gastrocnemius thickness to indicate the low SMI was calculated by a receiver operating characteristic curve analysis. Results: The low SMI rate was 16.9％ (n = 33). BMI was significantly lower (19.9 vs 22.5 kg/m 2 ; p < 0.01), the gastrocnemius thickness lower (11.0 vs 13.3 mm; p < 0.01), and CEI higher (97.5 vs 87.0; p = 0.02) in the low SMI group than those in the normal group. The gastrocnemius thickness was independently associated with the low SMI (OR, 0.584; 95% CI, 0.416–0.818; p < 0.01). The cut-off value of gastrocnemius thickness was <11.6 mm (AUC, 0.83; sensitivity, 0.83; specificity, 0.73; p < 0.01). Conclusion: Gastrocnemius thickness by ultrasonography was associated with low skeletal muscle mass, and the cut-off value to indicate the low skeletal muscle mass was revealed.